Inflammation and cognitive performance in first-episode schizophrenia spectrum disorders: The moderating effects of childhood trauma - Keřková, Barbora; Knížková, Karolína; Večeřová, Monika; Šustová, Petra; Fürstová, Petra; Hrubý, Aleš; Španiel, Filip; Rodriguez, Mabel (Schizophrenia research, 2023)
In this study, we aimed to determine whether childhood trauma moderated the relationship between inflammation and cognitive functioning in persons with first-episode schizophrenia spectrum disorders (SSDs). We included data from 92 individuals who participated in the nationwide Early-Stage Schizophrenia Outcome study. These individuals completed the Childhood Trauma Questionnaire, provided a fasting blood sample for high-sensitivity C-reactive protein analysis, and underwent extensive neuropsychological testing. The intervening effects of age, sex, education, smoking status, and body mass index were controlled. Results indicated that childhood trauma levels significantly moderated the relationship between inflammation and four cognitive domains: speed of processing, working memory, visual memory, and verbal memory. Inflammation also predicted verbal memory scores irrespective of childhood trauma levels or the covariates. Upon further exploration, the significant moderation effects appeared to be primarily driven by males. In conclusion, a history of childhood trauma may be an important determinant in evaluating how inflammation relates to the cognitive performance of people with first-episode SSDs, particularly in speed of processing, working memory, visual memory, and verbal memory. We recommend that future researchers examining the effect of inflammation on cognitive functioning in SSDs include trauma as a moderating variable in their models and further examine additional moderating effects of sex.
Keywords: schizofrenie; Schizophrenia; zánět; Neuropsychological Tests; neuropsychologické testy; Male; kognice; lidé; Inflammation; mužské pohlaví; nepříznivé zkušenosti z dětství; Humans; Adverse Childhood Experiences; Memory, Short-Term; Cognition; krátkodobá paměť